Intelligent Reflecting Surfaces for Underwater Visible Light Communications - Yalcin Ata; Hanaa Abumarshoud; Lina Bariah; Sami Muhaidat; Muhammad Ali Imran (IEEE Photonics Journal, 2023)
Intelligent reflecting surfaces (IRSs) offer paradigm shift towards enhancing the capabilities of wireless communications. The use of this emerging technology in the realm of underwater wireless systems is a promising solution to overcome the limitations pertinent to such challenging environments. In this paper, we quantify the performance enhancement offered by the integration of IRS technology in the context of underwater optical wireless communication (OWC). Specifically, we derive a closed-form expression for the outage probability over log-normal channels, taking into consideration the underwater attenuation, pointing error, and turbulence effects. The underwater turbulent medium is characterized by the recently introduced Oceanic Turbulence Optical Power Spectrum (OTOPS) model that uses the practical values of average temperature and salinity concentration in earth basins. The presented numerical results take into account the effects of the turbulent medium as well as the communication system parameters (i.e., communication range, receiver aperture diameter, number of IRS). Our results show that IRSs can offer significant enhancement in the reliability of underwater OWC systems under attenuation, beam displacement, and turbulence effects. Moreover, the combined effect of using a large number of reflecting surfaces and a larger aperture diameter yields a more noticeable improvement.